2022
DOI: 10.1186/s12905-022-01917-5
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial cancer with concomitant endometriosis is highly associated with ovarian endometrioid carcinoma: a retrospective cohort study

Abstract: Background Endometriosis is assumed to be involved in ovarian cancer development, which is called endometriosis-associated ovarian cancer (EAOC). Uterine endometrial cells may be the cell of origin of EAOC. Accumulated carcinogenic changes in the uterine endometrial cells may increase the risk of developing EAOC. To further understand the pathogenesis of EAOCs, we focused on the clinicopathological characteristics of EAOCs in endometrial cancer patients with concomitant endometriosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(42 reference statements)
0
3
0
Order By: Relevance
“… 16 Additionally, genomic studies have demonstrated that cancer-related genomic alterations are present in some endometriotic lesions, supporting the hypothesis that endometriosis is the origin of ovarian endometrioid and clear cell carcinoma. 12 , 15 , 24 …”
Section: Discussionmentioning
confidence: 99%
“… 16 Additionally, genomic studies have demonstrated that cancer-related genomic alterations are present in some endometriotic lesions, supporting the hypothesis that endometriosis is the origin of ovarian endometrioid and clear cell carcinoma. 12 , 15 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…It is known that the association between endometrial neoplasm and ovarian endometrioid cancer occurs in 3.1–10.0% of patients with endometrial cancer and in 10% of those with ovarian cancer [ 28 ]. In fact, in a recent retrospective cohort study by Ishizaka and colleagues has demonstrated that endometrial cancer associated with endometriosis has a high probability of being simultaneous at ovarian carcinoma, in particular, endometrioid histotype is the most common histological subtype present [ 29 ]. Moreover, different types of gene-based biomarkers such as ARID1A , PIK3CA , KRAS and CTNNB1 are recurrently mutated in endometrial cancer type I, endometriosis and endometriosis-associated ovarian tumors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this observation, the solid/cystic rate in the ECC group at macroscopic histology was significantly lower than the EAEOC group. Arguments against the theory by Kajihara et al include (i) the demonstration by various authors of the endometrioid histology in synchronous ovarian and endometrial carcinomas associated with endometriosis which is not consistent with the endometrioid tumor development from the Müllerian epithelium [ 29 , 30 ]; (ii) evidence supporting different origins for the various forms of endometriosis [ 8 ] does not tend to indicate two different histogeneses for the endometriotic cyst, as the theory of Kajihara and coworkers would imply. Endometriosis in different sites might indeed have a different histogenesis.…”
Section: Discussionmentioning
confidence: 99%